The Effectivence Of Healing Wound By Using Normal Saline (Nacl 0,9%) And Hydrogel For Diabetes Mellitus Patinets’ With Ulcer At District Of Semarang Hospital - S. Eko Ch. Purnomo; Sri Utami Dwiningsih; Ahmad Sugeng Prayitno (Jurnal Riset Kesehatan, 2013)
The raising of diabetes melitus has increased complication on diabetes, one of that occurence is the wound on patients’ foot (diabetic foot ulcer). There are three supporting factors to diabetic foot ulcer likes neurotic disturbance, infection, and flow of blood disturbance. Researchs showed the capability comparison of hydrogel in debridement on necrotic tissue with debridemen enzimatic, hydrogel has better result in debridement and granulation on the tissue grow faster. The purpose of this research is to find out the efectiveness of healing wound by using Normal Saline(NaCl 0,9%) and hydrogel for diabetes melitus patinets’ with ulcer.This research is a quantitave one with experimental design. Population of this research are all of the diabetes melitus patients’ with ulcer. Method of sampling is using purposive sampling which collected 30 respondent foe each group. This data prepared with independent t – test, but abnormality distribution of data, become use alternative analize is using Mann-Whitney U-test.The result of data analize by using Mann-Whitney U-test and 5% signification, with ρ = 0,000 with Z result : 6,482 and mean rank 45,08:15,92 (3:1) it means that hydrogel is more effective than normal saline in healing wound for diabetes melitus patinets’ with ulcer at District of Semarang Hospital. The mean repaired ulcer with hydrogel decrease mean 10-13 point and normal saline decrease 2-3 point on 9 days (Bates Jansen scale).Conclusion this woundcare with hydrogel 3 poit more effectiveness than normal saline on regenetaion tissues. This advice make hydrogel for woundcare diabetic ulcer or more ulcers.